ABO blood group, glycosyltransferase activity and risk of venous thromboembolism. Issue 193 (September 2020) - Ibrahim-Kosta, Manal; Bailly, Pascal; Silvy, Monique; Saut, Noemie; Suchon, Pierre; Morange, Pierre-Emmanuel; Chiaroni, Jacques; Trégouët, David-Alexandre; Goumidi, Louisa
Abstract: Introduction: ABO blood group influence the risk of venous thromboembolism (VTE) by modifying A and B glycosyltransferases (AGT and BGT) activities that further modulates Factor VIII (FVIII) and von Willebrand Factor (VWF) plasma levels. The aim of this work was to evaluate the association of plasma GTs activities with VWF/FVIII plasma levels and VTE risk in a case-control study. Materials and methods: 420 cases were matched with 420 controls for age and ABO blood group. GT activities in plasma were measured using the quantitative transfer of tritiated N -acetylgalactosamine or galactose to the 2′-fucosyl-lactose and expressed in disintegration per minute/30 μL of plasma and 2 h of reaction (dpm/30 μL/2H). FVIII and VWF plasma levels were respectively measured using human FVIII-deficient plasma in a 1-stage factor assay and STA LIATEST VWF (Diagnostica Stago). Results: A and B GT activities were significantly lower in cases than in controls (8119 ± 4027 vs 9682 ± 4177 dpm/30 μL/2H, p  = 2.03 × 10 −5, and 4931 ± 2305 vs 5524 ± 2096 dpm/30 μL/2H, p =0.043 respectively). This association was observed whatever the ABO blood groups. The ABO A1 blood group was found to explain~80% of AGT activity. After adjusting for ABO blood groups, AGT activity was not correlated to VWF/FVIII plasma levels. Conversely, there was a moderate correlation (ρ ~ 0.30) between BGT activity and VWF/ FVIII plasma levels in B blood group carriers. Conclusion: Work showed, for the first time, that GT activities were decreased in VTE patients in comparison to controls with the same ABO blood group. The biological mechanisms responsible for this association remained to be determined. Highlights: Glycosyltransferase activities were lower in patients with venous thrombosis. These lower activities were observed whatever the ABO group. ABO A1 group explained 80% of the A glycosyltransferase activity.